EKSISTENSI KOPERASI BAGI MASYARAKAT UMUM DI KELURAHAN LEMBAH DAMAI KOTA PEKANBARU - Fitria Kusuma Wardhani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
The purpose of this study is to understand and identify the existence of cooperatives for the general public in the village of Lembah Damai, Pekanbaru City. This research method is sociological law. the number of population available. Of the 8 cooperatives, researchers took samples of 3 cooperatives. The research method used is to use qualitative methods to describe descriptively the data that has been obtained. The inductive metodo conclusion is a way of thinking that draws a conclusion from a general statement or argument in a specific statement or proposition. Data is used are primary datos, namely primary datos, namely statutory regulations and secondary datas, namely Annual Cooperative Member Meetings and tertiary datas, namely literature. The purpose of this study is that the writer and the public can find out and understand Law Number 25 of 1992 concerning Cooperatives, namely in the form of services, namely transfer and exchange of knowledge in the field of management of pengas pengas. Skills are the skills of partners in developing solutions and goals of cooperatives as savings and loan institutions for the general public. The results of this study indicate that cooperatives can build community independence so as to reduce unemployment rates for usar micro, small and medium enterprises.